Influencing role of Demographic factors in Emotional and Behavioral Problems among School Children of Khyber Pakhtunkhwa Pakistan - Dr.Saima arzeen; Sara Ali; Dr. Nighat Shaheen (Journal of Peace, Development and Communication, 2023)
The aim of the present study is to examine the influencing role of demographic variables in emotional and behavioral problems among secondary high school children. The cross sectional and co-relational research design was used in current study to test the study hypothesis. The data was collected from 600 high school students with age range of 13-18 years. The data was collected from government and private secondary high schools of district Peshawar KPK. The Problem with School children Scale (PWSCS) Urdu version was used for the purpose of data collection. Multiple regression and independent t-test were used to analyze the data. The result showed that demographic variables such as (Socioeconomic status and family structure) are significantly positively predict emotional Problems while demographic variables (gender, medical illness and school type) are significantly negatively predicts emotional and Problems among secondary high school students. The study further revealed that demographic variables such as socioeconomic status and family structure positively associated with behavioral Problems and gender, medical illness and school type are significantly negatively predicts the behavioral Problems among secondary high school students. The study also revealed that private schools student’s face higher level of emotional and behavioral problems as compared to government school students.